THE INFLUENCE OF T.S.ELIOT’S POETIC TECHNIQUES ON MODERN UZBEK LITERATURE (Journal of Universal Science Research, 2025)
T.S. Eliot’s modernist poetry has significantly shaped global literary traditions, influencing themes, structures, and poetic techniques across various cultures. While much research has explored Eliot’s impact on Western literature, limited studies address his influence on Uzbek poetry. This article examines the extent to which Eliot’s poetic innovations—such as fragmentation, intertextuality, and mythological allusions—are reflected in modern Uzbek literature. Through a comparative analysis of Eliot’s major works (The Waste Land, Four Quartets) and selected Uzbek poetic texts, this study highlights stylistic and thematic parallels. The findings suggest that Eliot’s influence on Uzbek poetry is primarily indirect, often mediated through Russian and Western literary traditions.